Microwave-assisted hydrothermal synthesis of lead zirconate fine powders - Apinpus Rujiwatra (Maejo International Journal of Science and Technology, 2011)
A rapid synthesis of lead zirconate fine powders by microwave-assisted hydrothermal technique is reported. The influences of type of lead precursor, concentration of potassium hydroxide mineraliser, applied microwave power and irradiation time are described. The synthesised powders were characterised by powder X-ray diffraction, field emission scanning electron microscopy, energy-dispersive X-ray spectroscopic microanalysis and light scattering technique. The merits of the microwave application in reducing reaction time and improving particle mono-dispersion and size uniformity as well as the drawbacks, viz. low purity of the desired phase and increasing demand of mineraliser, are discussed in relation to conventional heating method.